A Comparison of Mindfulness Meditation and Cognitive Self-Observation - Greene, Yvonne; Hiebert, Bryan (Canadian Journal of Counselling and Psychotherapy, 2011)
Twenty-four college students learned either a meditation or a cognitive self-observation procedure. Both groups showed reliable increases in several dimensions of self-actualization (measured by the Personal Orientation Inventory) and decreases in many common stressrelated symptoms (measured by the Symptons of Stress Inventory). There were no differential treatment effects.